Violated by Rebels, Violated by Family: Returnee Girls of the Lord’s Resistance Army (LRA) in Northern Uganda - Khamalwa, Wotsuna (East African Journal of Traditions, Culture and Religion, 2022)
In the prologue to his book Frontiers of Violence in North-East Africa, Richard Reid recounts how in the first few years of the third millennium, the region of North-East Africa has been enmeshed in conflict. This region which includes Somalia, Ethiopia, Eritrea, and Southern Sudan has experienced intermittent violent conflicts and destruction by wars based on reasons and excuses ranging from ethnicity and religion, to political disagreements caused by thirst for power. This region also includes Northern Uganda, particularly Acholi-land, which was caught up in the throes of violent conflict since the mid- eighties, between the Lord’s Resistance Army (LRA) and the government of Uganda. For more than three decades, Acholi-land was engulfed in untold suffering, unleashed upon its population by foes from without and, tragically, attackers from within! An historical occupation of being exceptionally good soldiers that had stood them in good stead in colonial and post-colonial times turned out to be a curse they would always true!